Problem-oriented project-based learning an initiative to mould balance graduates - Fatmawati, Latada; Jamilah Bebe, Mohamad; Aini, Ahmad; Mansor, Sulaiman (2017)
The paper talks about the implementation of Problem-Oriented Project-Based Learning (POPBL) at University Malaysia Pahang. The approach was employed as one of the I-LEAD intervention program modules. The POPBL module incorporated students’ Soft Skills theoretical knowledge and its application to solve humanities issues around the campus. The participants were 32 students from various year of study chosen by their faculties based on specified characteristics. Working in the small group of 5-6 members, the participants were required to; (i) attend 6 hours critical thinking and problem solving discussion sessions (ii) prepare a problem identification plan based on designated theme, (iii) designed a project proposal complete with an action plan to solve the identified problem, (iv) implement the plan (v) prepare a complete report furnished with related documents and images and finally (vi) present the report orally. Assessment on technical aspect was based on project proposal and final report, while Soft Skills applications were observe through work process i.e., work progress (Leadership Skills), task distribution and coordination (Team Working), flow of communications (Communication Skills) time management (Ethics and Moral Professional) and quality of solution (Critical Thinking and Problem Solving). The findings advocate that on the technical aspect, students were moderately able to prepare a project report but they need lots of assistance in preparing project proposal particularly in analysing and identifying a problem. On Soft Skills application aspect, most students reported an adequate skills expansion particularly their team working and communication. Yet, the program also suggested shocking findings in relation to lecturers’ readiness and competence to do the assessment.